Electroconvulsive Therapy in Functional Hallucination: Scope and Challenges - Joshi, Sulochana; Shakya, Rabi (Case Reports in Psychiatry, 2017)
Functional hallucinations are hallucinations triggered by a stimulus in the same modality and cooccur with it. They are rare in occurrence; however, their rarity has no significance as psychopathology till date. Also, very little is known about the treatment of such hallucinations. Electroconvulsive therapy (ECT) has been tested for several psychiatric illnesses and has a few relative contraindications; however, it has not previously been used in treating functional hallucinations. We report on a female patient with paranoid schizophrenia who experienced functional hallucinations continuously despite the use of adequate risperidone, which controlled other symptoms. She was treated with ECT which resolved the functional hallucinations. The case highlights the need to ponder on the significance of the phenomenon as well as treatment of this psychopathology by ECT. It also underscores ECT as a treatment option for this kind of hallucination.